2002
DOI: 10.1007/s11661-002-0090-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding creep—a review

Abstract: A simple model based on the Orowan equation and the dynamic evolution of the dislocation structure by generation and merging of slipped areas is used to see which experimental results on creep of pure and solute-hardened crystalline materials can or cannot be explained with regard to creep with refinement or coarsening of the dislocation structure and steady-state creep. Quantitative deficiencies of the model for pure materials are discussed; most of them are related to neglection of subgrain formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(67 citation statements)
references
References 34 publications
1
63
0
3
Order By: Relevance
“…The static load might induce some creep in the metal, but this phenomenon is well known and its magnitude reduces over time. 8 Thus, we consider a cantilever subject to a time dependent force F(t), with a characteristic frequency below the macroscopical resonance of the cantilever. In this case, the local microscopic stress varies over time following the external drive.…”
Section: B Up-conversion Noise Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The static load might induce some creep in the metal, but this phenomenon is well known and its magnitude reduces over time. 8 Thus, we consider a cantilever subject to a time dependent force F(t), with a characteristic frequency below the macroscopical resonance of the cantilever. In this case, the local microscopic stress varies over time following the external drive.…”
Section: B Up-conversion Noise Modelmentioning
confidence: 99%
“…8 Although the underlying micro-mechanics of mechanical up-conversion and creep may be related, creep has a event rate that decreases quickly after the initial stress, and experimental investigations have shown that the creep can be reduced with the use of maraging steel. 1,2,6,11 Our experiment however focuses on mechanical events that are continuously triggered by a time varying external perturbation, such as the Advanced LIGO suspension cantilevers which are subjected to by the local micro-seismic activity of the ground.…”
Section: Introductionmentioning
confidence: 99%
“…Treating recovery of dipoles under the assumption of spatially homogeneous glide on the active slip systems [4,13,14] leads to a rate ε & s of steady-state deformation as function of stress σ and temperature T which reproduces some of the experimentally observed features. This is…”
Section: Low-angle Boundariesmentioning
confidence: 52%
“…Therefore the density ρ dip of dislocation dipoles, i.e. the length of dislocations which is stored in dipolar configuration, needs to be considered as a structure parameter entering the expression for dislocation recovery by annihilation: [4,13].…”
Section: Low-angle Boundariesmentioning
confidence: 99%
“…Studies of the effect of strain rate transients on the plastic behaviour of superplastic metals are scarce in the literature, 30,31) although the cases of hot working [32][33][34][35] and creep [36][37][38][39] conditions have been investigated more extensively. One common observation in the hot-working or creep studies is that conventional materials react to strain rate transients according to two typified behaviours: either ''pure metal'' or ''alloy'' type.…”
Section: Transient Strain Rate Effectsmentioning
confidence: 99%